Решить уравнение: sinx *cosx=6*(sinx-cosx-1)

August333 August333    3   23.05.2019 18:20    0

Ответы
harwq harwq  19.06.2020 12:33
6(sin(x) + cos(x)) - sin(2x) + 6 = 0 
6(sin(x) + cos(x) + 1) - sin(2x) = 0 
6(sin(x) + 2cos^2(x/2)) - sin(2x) = 0 
6sin(x) + 12cos^2(x/2) - 2sin(x)cos(x) = 0 
3sin(x) - sin(x)cos(x) + 6cos^2(x/2) = 0 
sin(x)(3 - cox(x)) + 6cos^2(x/2) = 0 
sin(x)(2 + 2sin^2(x/2)) + 6cos^2(x/2) = 0 
sin(x)(1 + sin^2(x/2)) + 3cos^2(x/2) = 0 
sin(x)cos^2(x/2) + 3cos^2(x/2) = 0 
cos^2(x/2)(sin(x) + 3) = 0 
Данное равенство будет обращаться в 0, только когда 
cos^2(x/2) = 0 
cos(x/2) = 0 
x/2 = p/2 + pk 
x = p + 2pk, k E Z
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра